Madrasah Digital: Transformasi Digital MAN 4 Tanah Datar Berbasis Budaya dan Lingkungan - Sudirman, Subhan Ajrin; Yuharnida, Yuharnida; Rizqullah, Muhammad Naufan; Lestari, Novia; Riza, Ozzy Secio; Putra, Rahman Pranovri; Putra, Razaq Aulia (Universitas Muhammadiyah Mataram, 2026)
Abstract: This community service programme aims to produce a blueprint for a culture- and environment-based digital madrasah model as a strategic guideline for the development of sustainable digital education at MAN 4 Tanah Datar. The community service method uses a participatory qualitative approach with an Asset-Based Community Development (ABCD) framework, which emphasises the exploration and optimisation of local assets and potential as the basis for the madrasah's digital transformation. This approach was chosen to ensure that the development process did not start from a perspective of deficiency, but rather from the social, cultural, and environmental strengths that the madrasah community already possessed. The ABCD stages include defining, discovering, dreaming, asset mapping, linking and mobilising assets, and monitoring, which were carried out collaboratively with teachers, madrasah leaders, students, and community leaders. Data collection is carried out through participatory observation, in-depth interviews, Focus Group Discussions (FGD), and documentation studies to gain a comprehensive understanding of the conditions, potential, and challenges of madrasah digitalisation. The entire process is reinforced by the Logical Framework Approach (LFA) to develop systematic, measurable, and sustainable programme planning. The combination of ABCD and LFA enables the development of a contextual, participatory blueprint for digital madrasahs that is in line with cultural values and environmental concerns.Abstrak: Program pengabdian masyarakat ini bertujuan menghasilkan sebuah blueprint model madrasah digital berbasis budaya dan lingkungan sebagai pedoman strategis pengembangan pendidikan digital berkelanjutan di MAN 4 Tanah Datar. Metode pengabdian menggunakan pendekatan kualitatif partisipatif dengan kerangka Asset-Based Community Development (ABCD), yang menekankan penggalian dan optimalisasi aset serta potensi lokal sebagai dasar transformasi digital madrasah. Pendekatan ini dipilih untuk memastikan proses pengembangan tidak berangkat dari perspektif kekurangan, melainkan dari kekuatan sosial, budaya, dan lingkungan yang telah dimiliki komunitas madrasah. Tahapan ABCD meliputi define, discovery, dream, asset mapping, linking and mobilizing assets, serta monitoring, yang dilaksanakan secara kolaboratif bersama guru, pimpinan madrasah, siswa, dan tokoh masyarakat. Pengumpulan data dilakukan melalui observasi partisipatif, wawancara mendalam, Focus Group Discussion (FGD), serta studi dokumentasi guna memperoleh pemahaman komprehensif terkait kondisi, potensi, dan tantangan digitalisasi madrasah. Seluruh proses tersebut diperkuat dengan Logical Framework Approach (LFA) untuk menyusun perencanaan program yang sistematis, terukur, dan berkelanjutan. Kombinasi ABCD dan LFA memungkinkan penyusunan blueprint madrasah digital yang kontekstual, partisipatif, dan selaras dengan nilai budaya serta kepedulian lingkungan.